Experiência de fé e o seguimento de Cristo em Dietrich Bonhoeffer - Lima, Anderson (2014)
This thesis reflects on the theme of Faith Experience and Discipleship, analyzed from the perspective of the theologian Dietrich Bonhoeffer. We seek to determinate how the experience of faith actually influences the genuine walk with Christ. In support of the issue, we have come through a literature review of the life and work of Dietrich Bonhoeffer. The first chapter discusses the historical context in which Bonhoeffer was inserted, as wars, the interwar period and Christianity, besides his biography. In the second chapter, from an analysis of his works, we seek to present his theology from the perspective of the experience of faith. In the third and final chapter, the focus is the experience of faith and discipleship of Christ itself. Analyzes the concepts, Dietrich Bonhoeffer and his experience of faith, salvation and martyrdom, and a brief analysis of the Theology and Pentecostal movement, helping to affirm the need for a genuine experience of faith to a real following of Christ.